The Use of Botulinum Toxin Type A in the Healing of Thyroidectomy Wounds: A Randomized, Prospective, Placebo-Controlled Study. Issue 2 (February 2019) - Phillips, Timothy J.; Fung, Elaine; Rigby, Matthew H.; Burke, Emily; Hart, Robert D.; Trites, Jonathan R. B.; Gassner, Holger G.; Taylor, S. Mark
Abstract : Background: Recent research has indicated that botulinum toxin type A may have an inhibitory effect on the formation of fibroblasts and thus possibly decreases the severity of scar formation. Therefore, a trial was designed to assess the effects of botulinum toxin type A on scar formation after thyroid surgery. Methods: A double-blind, randomized, controlled trial was designed. All patients underwent a preoperative survey to assess scar history. All patients underwent a total thyroidectomy, hemithyroidectomy, or parathyroidectomy through a standardized incision. At the conclusion of the case, one half of the incision was injected with botulinum toxin type A, and the other half was injected with saline (placebo). The scars were then evaluated at 4 weeks, 6 months, and 1 year postoperatively using subjective scar analysis scales. Results: A total of 40 patients were enrolled. There was no significant difference in scarring at any of the time points between the botulinum toxin type A–treated and placebo sides of the incision. A subgroup analysis was performed that examined the effects of botulinum toxin type A on those with a severe scar history. This demonstrated a significant decrease in scarring at 6 months postoperatively on the botulinum toxin type A–treated side. Conclusions: This study indicates that botulinum toxin type A administration immediately after surgical closure of a thyroid incision does not demonstrate a difference in scar outcomes compared with the control side. However, there was less scarring in subjects who had a severe scar history. This study found opposite results to a similarly designed study. Further study is required to determine the optimal use of botulinum toxin type A for wound healing. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.